The museum internship as an analogous learning space for preservice teacher education. (June 2019) - Cuenca, Alexander; Gilbert, Lisa
Highlights: This study explores a museum internship program as a non-school context for learning to teach. For the participants featured in this study, the internship was a positive developmental learning experience. The internship influenced pre-service teachers' identities, perspectives, and pedagogies. The internship also helped catalyze, crystallize, and diversify the experience of learning to teach. Internships with museum educators can serve as important analogous learning spaces for teacher education.